The Spreading of Alternatives: Is it the Perceived Choice or Actual Choice that Changes our Preference?. (31st May 2016) - Luo, Jiayi; Yu, Rongjun
Abstract: After making a difficult choice, the preference rating of a chosen alternative tends to increase, and the rating of the rejected one tends to decrease. Such a change of preference is called spreading of alternatives. It is unclear whether it is the choice itself, or the choice one believes one has made that leads to preference change. Using a facial attractiveness task, we addressed this question by setting up an experiment to measure how the actual choice and perceived choice changed the preference. In the current study, participants first rated the attractiveness of female faces, and then made a choice between two faces that they had rated the same, after which, they re‐rated the female faces. Notably, in the re‐rating session, participants were given either veridical, false, or no feedback about their prior choice. This way, we were able to measure the functions of actual choice and perceived choice in rating changes. Results showed that both actual action and perceived action exert significant influence in shaping preference. The veridical feedback enhanced the spreading of alternatives effect whereas the false feedback weakened this effect, indicating that preference can be modulated by explicit manipulation. Copyright © 2016 John Wiley & Sons, Ltd.